2008
DOI: 10.1158/1078-0432.ccr-07-1811
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Succinate Induces Ceramide-Mediated Apoptosis in Head and Neck Squamous Cell Carcinoma In vitro and In vivo

Abstract: Purpose: Vitamin E succinate (a-TOS) inhibits the growth of cancer cells without unacceptable side effects.Therefore, the mechanisms associated with the anticancer action of a-TOS, including ceramide-mediated apoptosis, were investigated using head and neck squamous cell carcinoma (HNSCC) in vitro and in vivo. Experimental Design: Five different human HNSCC cell lines (JHU-011, JHU-013, JHU-019, JHU-022, and JHU-029) were treated with a-TOS, and its effects on cell proliferation, cell cycle progression, cerami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Liposomal curcumin suppresses HNSCC growth in vitro and in vivo via an AKT-independent pathway (29). Vitamin E succinate also inhibits HNSCC growth and viability in vivo and in vitro (30). Testing these agents alone and in combinations (possibly including mTOR inhibitors) in the oral-specific mouse model would be a logical step in evaluating their potential for oral cancer prevention.…”
mentioning
confidence: 99%
“…Liposomal curcumin suppresses HNSCC growth in vitro and in vivo via an AKT-independent pathway (29). Vitamin E succinate also inhibits HNSCC growth and viability in vivo and in vitro (30). Testing these agents alone and in combinations (possibly including mTOR inhibitors) in the oral-specific mouse model would be a logical step in evaluating their potential for oral cancer prevention.…”
mentioning
confidence: 99%
“…In HNSCC, Gu et al showed promising anticancer effects of vitamin E succinate to inhibit HNSCC growth and viability via ceramide-mediated apoptosis. This was found in both cancer cells and in a xenograft cancer mouse model (89). Other groups have attempted to find ways to deliver ceramide into HNSCC cells successfully (90).…”
Section: ------------------------------------------------------------mentioning
confidence: 81%
“…At present, the mechanism underlying the effect of VES and TS-1 on activating PP2A phosphatase activity remains unclear. We hypothesize that this PP2A activation might be attributed to increased intracellular levels of ceramide, a known PP2A activator, in drugtreated cells since VES has been reported to stimulate ceramide production (13,23). The ability of VES and TS-1 to mediate ceramideinduced PP2A activation is currently under investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Substantial evidence indicates that VES exhibits a unique ability to target multiple signaling pathways associated with carcinogenesis, tumor progression and metastasis , including those mediated by nuclear factor kappaB (17,24), protein kinase Ca (25), sphingolipids (13,23), Bcl-2/Bcl-xL (16), androgen receptor (AR) (10), vascular endothelial growth factor (7) and insulin-like growth factor-binding protein-3 (22). Although some of these signaling targets might be cancer type specific, this broad spectrum of action in conjunction of low toxicity underlies the therapeutic value of developing VES into useful agents for cancer treatment or prevention.…”
Section: Introductionmentioning
confidence: 99%